Pengaruh Variasi Suhu dan Waktu Pada Proses Nitridasi Terhadap Perubahan Sifat Mekanis Baja St 40 - Trisbenheiser Trisbenheiser (Jurnal Teknik Mesin Sinergi, 2022)
This research aimed to determine the changes of strength, micro structure, and wearing out of  St 40 after nitriding process using the urea fertilizers as the sourcse of nitrogen. In this research, the process of nitridation was carried out using the variation of temperature of 4500C, 5000C, and 5500C, and the variation of endurance time of 1 hour, then 3 hours, and 5 hours. The experiment results indicated that the highest hardness value of the steel ST 40 at the temperature of 5500C were consecutively for the endurance time of 1 hour, 3 hours, and 5 hours were 115,46 HB, 116,30 HB, and 116,51 HB.  The increase in the surface hardness of the specimen is affected by the increase in temperature and holding time. Meanwhile, the results of the smallest wearing out of the steel ST 40 at temperature of 5500C with the endurance time 5 hours were consecutively at the wearing out time of 60 minutes, 90 minutes, and 120 minutes were 0,38 mm3/ minute, 0,44 mm3/minute, and 0,57 mm3/minute. The value of the wearing out on the specimen is affected by temperatue and holding time during nitriding.  As for the results of the obsevation using the microscope at the micro structure of stell St 40 after undergoing nitiridation, showed an increase of number of fasa perlite at the specimen surface, the higher the heating temperature the more the fasa perlits formed, this is directly roportional with the hardness of the specimen surface.The fasa perlite formed has better hardness than of fasa ferrite.